(3SDGdGJ dHYV GdCaGVds - (3Gdehdi EHQGgjes; (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO def jLjH SDGd ef GfJgei Edi HGHg hHYO aGYdehG eYGTQ WdGH djbjf SdGe Ydjce dGjfJai GdLGgjf Cf GdeNJUQ GdPi ShOg s
(3BNQgG (B:s
(3HOdjd jOd dYi NdGa eG PcQg UOQ GdTQjYI hZjQg ef GdCaGVd aYdjce HGdGNJjGQ HgG CjgG GdaVdGA Ke GdGNJHGQ JeJ GdefGbTI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B25s
(3EUdGM GdhbGjI (B" (3GfXQ cTa GdXfhf L(B1 (3U` (B109s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hgj GYJQGVGJ Ydi GHf ceGd HGTG ai cJGHg GdCUdGM hGdEjVGM ddehdi EHQGgje GdeYRhd ef eOQSI SdjeGf HGTG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
Keywords: (3GdeLGejYs